Biased Recognition of Surprised Facial Expressions Following Awake Craniotomy of a Right Temporal Lobe Tumor - Midorikawa, Akira; Saito, Shoko; Itoi, Chihiro; Ochi, Ryuta; Hiromitsu, Kentaro; Yamada, Ryoji; Shinoura, Nobusada (Frontiers in Psychology, 2019)
Lesion studies have shown that the right temporal lobe is crucial for recognition of facial expressions, particularly fear expressions. However, in previous studies, premorbid abilities of the patients were unknown and the effects of epileptic discharge could not be excluded. Herein, we report a case of a patient who underwent assessments of facial recognition before and after brain surgery and exhibited biased recognition of facial expressions. The patient was a 29-year-old right-handed male who underwent an awake craniotomy. Compared with the preoperative assessment, after the surgery, he showed biased recognition of surprised facial expressions, and his ability to recognize other facial expressions either improved or remained unchanged. These findings support the idea that the right temporal lobe is crucial for the recognition of facial expressions of surprise and that functional connectivity between various brain regions plays an important role in the ability to recognize facial expressions